Persepsi Siswa Terhadap Pelaksanaan Kegiatan Pembelajaran Pendidikan Jasmani, Olahraga dan Kesehatan (PJOK) Pada Kelas VII-VIII di SMP Kristen Palangka Raya - Kowaas, Rafael (Jurnal Keolahragaan JUARA, 2022)
The perception caused by students in grades VII-VIII OF Christian Junior High School shows differences in concepts in response to the implementation of physical education learning activities, this study aims to determine students' perceptions of the implementation of Physical Education, Sports and Health (PJOK) learning activities in grades VII-VIII at Palangka Raya Christian Junior High School. This research is a quantitative descriptive research with survey method. The conclusion of this study is students' perceptions of the implementation of Physical Education, Sports and Health (PJOK) learning activities in grades VII-VIII at Palangka Raya Christian Junior High School that, 1 student with a very good category of 4.2%, 10 students with a good category of 41.7%, 6 students with a medium category of 25.0%, 4 students with a category of less 16.7% and 3 students with a very less category of 12.5%. Therefore, from these results, it can be concluded that student’s perceptions of the implementation of Physical Education, Sports and Health (PJOK) learning activities in grades VII-VIII at Palangka Raya Christian Junior High School are categorized as good.